Pharmacological activity of the essential oil of Satureja viminea (Lamiaceae) - Suárez, Adriana; Echandi, María Mercedes; Ulate, Guido; Cicció, José Fco (Revista de Biología Tropical, 2003)
The aqueous extract and the essential oil of Satureja viminea (Lamiaceae) were tested. General physiologic effects were assessed through the Hippocratic screening test. Non fasted female Sprague Dawley rats were utilized and 250, 500, 750 and 1000 mg/kg doses were used. Two animals were used for each dosage level and for the vehicle alone. Exploratory behavior and curiosity were measured using a hole board apparatus and placing non-trained mice on the board and recording the number of holes explored in a 5 minute period. The Boissier chimney test was used to evaluate motor coordination. Muscle strength was assessed through a grasping test where mice were hung by their fore-limbs 40 cm above the base on a horizontal metal stainless bar. In all these tests, 3 groups of 6 albino mice, were treated with 1000 mg/kg of each the essential oil of S. viminea, the vehicle and diazepan (1 mg/kg) as a positive control. Analgesic activity was explored in Sprague-Dawley rats. The tail flick method described by D`Amour and Smith (1941) modified by CYTED was implemented on three groups (6 rats each) of animals treated with, each the essential oil of S. viminea (1000 mg/kg), the vehicle and indomethacine. The test was carried out just before and 30, 60 and 120 min after oral treatment. Peristaltic activity was measured in albino mice, three groups of 6 animals each, treated orally with each the essential oil of S. viminea (1000 mg/kg), the aqueous extract (1000 mg/kg), and the vehicle. The marker used was activated carbon. Animals were sacrificed 30 min after the marker was given and the percent of total small intestine traversed by it was calculated. Also a lethal dose 50 (LD 50) was determined with the Spearman-Karber method. A dose-related spontaneous motor activity reduction was observed. Exploratory behavior and curiosity were diminished. The grasping strength of mice was reduced. A very clear and significant analgesic effect was observed with the oral administration of the essential oil of S. viminea (1000 mg/kg). This effect is compared to that of indomethacine. Intestinal transit and gastric emptying were inhibited by the essential oil. The LD50 of the essential oil of S. viminea is 556.8 mg/kg.